Keeping up with the stress of antibody production: BAFF and APRIL maintain memory plasma cells. (August 2021) - Cornelis, Rebecca; Chang, Hyun-Dong; Radbruch, Andreas
Abstract : Memory plasma cells, also called long-lived plasma cells, provide 'humoral immunity' by continued secretion of protective antibodies against pathogens, which the immune system has once encountered. They are maintained mainly in the bone marrow, docking on to stromal cells individually. In those niches they can apparently persist for decades (Chang et al., 2018 [1]). Integrin-mediated contact to the stromal cell provides an essential survival signal to the plasma cell, activating the PI3K signalling pathway, downregulating FoxO1/3a and repressing the activation of caspases 3 and 7. In a redundant form, the cytokines BAFF and APRIL, ligands of the plasma cell receptors TACI and BCMA, provide a second essential survival signal, preventing activation of caspase 12, as triggered by endoplasmic reticulum stress.